Simulacrum in the tensions and disputes of the feminine and masculine in Montaña adentro by Marta Brunet - García, Francisco (Árboles y Rizomas, 2020)
This article reviews the strategies that Marta Brunet employs in her novel Montaña adentro (1923) to situate her work’s validity within the confines of the literary canon at that time. To support her project, she creates tensions between the feminine and masculine and uses a variety of masks in her writing. This lets her achieve a significant position in the cultural field dominated by male conceptions and assumptions. Montaña adentro is proposed as a site for the reader’s interpretation of a simulacrum within the permanent contention between the feminine and the masculine that ultimately shape her writing project.